Risk stratification of delayed causative aneurysm detection and long-term outcome in angiographically negative spontaneous subarachnoid haemorrhage - Shuo Wang; Jie Wang; Ji-Zong Zhao; Yong Cao; Jian-Feng Meng (Stroke and Vascular Neurology)
Background The risk factors of aetiology and poor outcome in angiographically negative subarachnoid haemorrhage (anSAH) were unclearly.Methods The authors performed a retrospective review of a prospectively maintained database for anSAH patients between 2014 and 2018. AnSAH was defined as SAH presents in CT with no underlying vascular abnormality on initial digital subtraction angiography (DSA) within 72 hours of admission. Baseline and follow-up information, including medical history, bleeding pattern (perimesencephalic angiogram-negative SAH (PAN-SAH) and non-PAN-negative SAH (NPAN-SAH)), modified Fisher Scale (mFS), Glasgow Coma Score (GCS), Hunt-Hess grade, repeated imaging and causative vascular lesions and follow-up modified Rankin Scale (mRS) were reviewed. Poor outcome was defined as mRS scored 3–6 at last clinical follow-up.Results Among 303 enrolled patients, 272 patients underwent at least once repeated imaging examination (median follow-up time, 3.0 months). Twenty-one (7.7%) aneurysms were detected. Multivariate logistic analysis showed that NPAN-SAH and mFS 3–4 were associated with a high rate of aneurysm detection in anSAH patients. Based on risk stratification, the aneurysm detection rate in the high-risk group (both NPAN-SAH and mFS 3–4) was as high as 20.370 per 100 person-years. Furthermore, of 251 non-aneurysm anSAH patients, after a total follow-up time of 1265.83 patient-years, poor outcome occurred in 18 (7.2%) patients. Multivariate Cox analysis found that NPAN-SAH and GCS 3–12 were associated with a high rate of poor outcome of anSAH. The cumulative 5-year incidence rate for poor outcome in the non-aneurysm anSAH patients in the high-risk group (both NPAN-SAH and GCS 3–12) was as high as 75.302 per 100 person-years.Conclusions Even in anSAH confirmed by initial DSA, patients with NPAN-SAH and mFS 3–4 should be monitored for delayed causative aneurysm detection, meanwhile in non-aneurysm anSAH patients, NPAN-SAH and initial functional impairment are associated with poor prognosis.